Walt Whitman and the making of Jewish American poetry - Barnat, Dara (Iowa Whitman series., 2023)
"Walt Whitman, though not a Jewish poet, has served as a crucial figure within the tradition of Jewish American poetry, starting in the mid-nineteenth century, until today. However, the genealogy of Jewish American poets responding to Whitman is wider and more nuanced than often recognized. Due to Allen Ginsberg's overt adoption of Whitman, it is often believed that Ginsberg is the only Jewish American poet to have engaged with Whitman's poetic style and democratic ethos. This book reveals how the lineage of poets responding to Whitman extends far beyond Ginsberg, and that Ginsberg himself receives Whitman through earlier Jewish American poets, like Charles Reznikoff. This project presents such a genealogy of poets in dialogue with Whitman (and each other), from Emma Lazarus and Adah Isaacs Menken, through twentieth-century poets, such as Charles Reznikoff, Karl Shapiro, Kenneth Koch, Muriel Rukeyser, Adrienne Rich, Marge Piercy, and Alicia Suskin Ostriker, Gerald Stern, and beyond. By researching Whitman's role in this tradition systematically, in the work of individual poets, and in the framework of Jewish American poetry more broadly, this book seeks to fill a gap in the understanding of these dynamics, and to invite other scholars to examine the Whitman-Jewish connection. A major finding in this book is that Whitman has been adopted by Jewish American poets as a liberal symbol against elements in High Modernist literary culture, which the poets perceived to be exclusionary and anti-Semitic. Thus, there is a negotiation of the vexed territory of being Jewish in America through an alignment with Whitman. As such, the turn to Whitman serves as a mode of exploring Jewish and American identity, whereby Walt Whitman the poet is imagined to be Jewish and American"--